Venous and Arterial Thromboses: Two Sides of the Same Coin? - Lippi, Giuseppe; Favaloro, Emmanuel J. (Seminars in Thrombosis and Hemostasis, 2018)
Arterial and venous thromboses are sustained by development of intraluminal thrombi, respectively, within the venous and arterial systems. The composition and structure of arterial and venous thrombi have been historically considered as being very different. Arterial thrombi (conventionally defined as “white”) have been traditionally proposed to be composed mainly of fibrin and platelet aggregates, whilst venous thrombi (conventionally defined as “red”) have been proposed as mostly being enriched in fibrin and erythrocytes. This archaic dichotomy seems ever more questionable, since it barely reflects the pathophysiology of thrombus formation in vivo. Both types of thrombi are actually composed of a complex fibrin network but, importantly, also contain essentially the same blood-borne cells (i.e., red blood cells, leukocytes, and platelets), and it is only the relative content of these individual elements that differ between venous and arterial clots or, otherwise, between thrombi generated under different conditions of blood flow and shear stress. Convincing evidence now suggests that either white or red intracoronary thrombi may be present in patients with myocardial infarction and, even more importantly, red thrombi may be more prone to distal embolization during percutaneous coronary intervention than those with lower content of erythrocytes. Conversely, it is now accepted that components traditionally considered to be involved “only” in arterial thrombosis are also represented in venous thrombosis. Thus, platelets comprise important components of venous clots, although they may be present in lower amounts here than in arterial thrombi, and von Willebrand factor is also represented in both arterial and venous thrombi. Of importance, such evidence thus supports the concept that adjunctive treatment normally associated to prevention of arterial thrombosis (e.g., aspirin) may have a role also in prevention and treatment of venous thrombosis.
Keywords: hemostasis; thrombosis; cardiovascular disease; venous thromboembolism; arterial thrombosis; blood coagulation